NEW TRENDS AND DEVELOPMENTS IN EDUCATIONAL TECHNOLOGY RESEARCH - MANJULA, Dr. V.S. (IJRDO -Journal of Computer Science Engineering, 2016)
Educational Technology research has moved through several stages of focusing at the beginning on the content to be learned, then on the format of instructional messages and, finally on the interaction between computers and students. A great majority of the theses employed quantitative paradigm, and qualitative studies made about one fourth of the total studies. The present paper reviews the research in technology-based learning environments in order to give both a historical perspective on educational technology research and a view of the current state of this discipline. To conclude that 1) trends in educational technology research were forged by the evolution of learning theories and the technological changes 2) a clear shift from the design of instruction to the design of learning environments can be noticed 3) there is a positive effect of educational technology on learning, but the size of the effect varies considerably 4) learning is much more dependent on the activity of the learner than on the quantity of information and processing opportunities provided by the environment. The most frequently investigated topics were computer-assisted instruction, alternative teaching and learning approaches, web-based learning, difficulties in integrating information technologies into educational practice, Internet-based learning, and distance education